Identification of Orthopedic Injuries Rehabilitation Needs in Bam Earthquake - Vahid Nejati; Seyyed Mohammad Ebrahim Mousavi; Mohammad Reza Soroush (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: The purpose of this study is identification of rehabilitation needs in orthopedic injuries of bam earthquake. Materials & Methods: In this cross sectional study we examined 3000 Persons of the injured people of the Bam earthquake who were referred to the hospitals of the country. We selected some of hospitals randomly and evaluated history of all patients that had been injured by earthquake. Results: Data shows that the most injuries are because of fracture and dislocation (63.74%). then, the traumatic injuries of the peripheral and central nervous system have the most penetration. (11.15 % and 9.53%) and the other cases including soft tissue injuries (3.17%), open wound (9.48%), arterial injuries (0.72%) and amputee have the least of all (0.55%). Conclusion: The practical conclusion for critic management is that the most needed experts are orthopedic and rehabilitation experts (physiotherapists and technical orthopedists), the emergency rehabilitation clinic are required for prompt rehabilitation services too.